Organoleptic Test and Iron Level Test Tofu Moringa meatballs as an alternative snack for Teenage Girls - Zida Shabrina Akmalia; Juliana Christyaningsih; Nur Hatijah; Annas Buanasita (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Many teenage girls in Indonesia suffer from anemia, prompting exploration into alternative dietary interventions. Moringa leaves, known for their high iron content, offer a potential solution. This study aimed to formulate tofu meatballs enriched with moringa flour, evaluating their iron content and organoleptic qualities as a feasible iron supplement for adolescent girls. Three tofu meatball formulations were tested: F1B with no added moringa flour, F2B with 5 g, and F3B with 10 g. Iron content was assessed using ICP-OES, and organoleptic tests were conducted. Statistical analysis included the Kruskal-Walli’s test, with Mann-Whitney test for significant differences. Results revealed F2B had the highest iron content at 1.34 mg/100 g, followed by F1B at 1.06 mg/100 g, and F3B at 1.23 mg/100 g. However, iron levels per serving fell short of the 10% daily requirement. While F1B was preferred for taste, aroma, color, and texture, F2B and F3B were still acceptable. Future improvements could involve using boiled moringa leaves and seasoning to enhance organoleptic qualities.